2020
DOI: 10.1016/j.surfcoat.2020.125412
|View full text |Cite
|
Sign up to set email alerts
|

Surface performances of Ti-6Al-4V substrates coated PVD multilayered films in biological environments

Abstract: Multilayered and nanostructured coatings of Ti based alloys (oxides and nitrides) are elaborated and tested for increasing protective properties such as corrosion and wear resistances. A pin-on-disc tribometer was used to evaluate the wear resistance in Hank's solution against bovine bone. Corrosion behavior in Hank's solution was determined by potentiodynamic and electrochemical impedance spectroscopy techniques. Besides, the specimen surfaces were characterized by Atomic Force Microscopy (AFM), Scanning Elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Greater mechanical properties, corrosion resistance, and biocompatibility occurred with the upgrade of the N/Ti ratio. In the work of Bahi et al (2020) , two types of coatings were studied: TiN as the top layer, while the upper layer of the others was TiO 2 with two different oxygen content. The TiN presents the best tribological performance in the multilayered film condition when its surface slide against the bovine cortical bone.…”
Section: Physical Modificationmentioning
confidence: 99%
“…Greater mechanical properties, corrosion resistance, and biocompatibility occurred with the upgrade of the N/Ti ratio. In the work of Bahi et al (2020) , two types of coatings were studied: TiN as the top layer, while the upper layer of the others was TiO 2 with two different oxygen content. The TiN presents the best tribological performance in the multilayered film condition when its surface slide against the bovine cortical bone.…”
Section: Physical Modificationmentioning
confidence: 99%
“…is phenomenon was also observed by Yousfi [17], where it was assumed that it is the cause of COF instability. In addition, a recent study by Bahi et al [12] showed that the COF for TiN/TiO 2 multilayer coating of Ti-6Al-4V substrate to be unstable COF as sliding distance increases. From Figure 7, it can be understood that there is a tendency for COF to decrease as load increases.…”
Section: Analysis Of Wear Mass Loss Anova Analysis Is Used To Evaluate Input Factors On Wmlmentioning
confidence: 99%
“…Ti and Ti alloys are lightweight and have improved biocompatibility and corrosion resistance, making them popular in medical and dental applications [11]. Protecting Ti-6Al-4V substrates with PVD coatings has been shown to improve mechanical characteristics, biocompatibility, osseointegration, wear, and corrosion resistance [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Ti-based intermetallic thin films could combine promising biocompatibility and high durability [ 18 , 20 ]. Among several available techniques, physical vapor deposition (PVD), e.g., sputtering, is one of the most commonly used techniques to coat implants [ 21 ], as the films produced by the sputtering process have very low surface roughness, which also play an important role on biofilm adhesion on Ti-based thin films [ 22 , 23 , 24 ]. The addition of several metallic elements during processing can improve the properties of pure Ti by the formation of intermetallic compounds.…”
Section: Introductionmentioning
confidence: 99%